2013
DOI: 10.1021/ol400046n
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (+)-Reserpine

Abstract: A catalytic, enantioselective synthesis of (+)-reserpine is reported. The route features a highly diastereoselective, chiral catalyst-controlled formal aza-Diels–Alder reaction between a 6-methoxytryptamine-derived dihydro-β-carboline and an enantioenriched α-substituted enone to form a key tetracyclic intermediate. This approach addresses the challenge of setting the C3 stereogenic center by using catalyst control. Elaboration of the tetracycle to (+)-reserpine includes an intramolecular aldol cyclization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 35 publications
0
33
0
2
Order By: Relevance
“…Indole alkaloids possess an array of complex molecular architectures that are able to produce diverse biological activities; this class of natural products has intrigued scientists for decades. [50][51][52][53][54] To tal synthesis efforts date back to the elegant construction of (AE)-reserpine [52] reported in 1956 by Woodward et al,a nd continuet oi nspire the development of new synthetic methods and approaches [53] today,i ncluding the total synthesis of (+ +)-reserpine reportedi n2 013b yJ acobsen et al [54] As alternative synthesis approaches have emerged to drive biological discoveries, indoles have remained of considerable interestb ecause unnatural indole small molecules have demonstrated impressive biological activities in diverse disease areas of importance to human health.S ynthetic efforts have led to the discovery of indoline compounds capable of resensitizing methicillin-resistant S. aureus to methicillin [55,56] whereas indole-inspiredB IOS has led to the identification of inhibitors of protein phosphatases, which are important drug targets for diabetes and cancer. [19] BIOS efforts have also led to the discovery of spirooxindole small molecules that influencen euronal network formation and demonstrate neurite outgrowth-promoting activities.…”
Section: Biological Investigationso Fy Ohimbine-derived Small Moleculesmentioning
confidence: 99%
“…Indole alkaloids possess an array of complex molecular architectures that are able to produce diverse biological activities; this class of natural products has intrigued scientists for decades. [50][51][52][53][54] To tal synthesis efforts date back to the elegant construction of (AE)-reserpine [52] reported in 1956 by Woodward et al,a nd continuet oi nspire the development of new synthetic methods and approaches [53] today,i ncluding the total synthesis of (+ +)-reserpine reportedi n2 013b yJ acobsen et al [54] As alternative synthesis approaches have emerged to drive biological discoveries, indoles have remained of considerable interestb ecause unnatural indole small molecules have demonstrated impressive biological activities in diverse disease areas of importance to human health.S ynthetic efforts have led to the discovery of indoline compounds capable of resensitizing methicillin-resistant S. aureus to methicillin [55,56] whereas indole-inspiredB IOS has led to the identification of inhibitors of protein phosphatases, which are important drug targets for diabetes and cancer. [19] BIOS efforts have also led to the discovery of spirooxindole small molecules that influencen euronal network formation and demonstrate neurite outgrowth-promoting activities.…”
Section: Biological Investigationso Fy Ohimbine-derived Small Moleculesmentioning
confidence: 99%
“…102 An efficient synthesis of isomukonidine (252), clausines L (253) and V (254), mukonidine (255), glycosinine (256), and mukonal (257) was reported, using the gold-catalyzed cyclization of indolyl-2,3-allenol 258 to carbazole 259 as a key step (Scheme 62). 103 The synthesis of 1-oxygenated carbazole alkaloids, clausine E (260) and mukonine (261), were achieved by anionic [4 + 2] annulation of lithiated furoindolones 262 with dimethyl maleate leading to carbazole 263 (Scheme 63). 104 Carbazomycin G (264), featuring a unique quinol moiety, was isolated from Streptoverticillium ehimense H 1051-MY 10.…”
Section: Indole Phytoalexinsmentioning
confidence: 99%
“…The tetracyclic intermediate 814 was assembled by a thiourea-catalyzed diastereoselective formal aza-Diels-Alder reaction between dihydro-b-carboline and enantioenriched enone (Scheme 169). 261 The total synthesis of rac-hirsutine (816) was achieved using phosphine-catalyzed [4 + 2] annulation as the key step. Cycloaddition between imine 817 and allenoate 818 in the presence of PBu 3 provided tricyclic intermediate 819, which was converted to rac-816 through the formation of the C-ring via an intramolecular alkylation and diastereoselective addition of the malonate anion (Scheme 170).…”
Section: Tryptaminesmentioning
confidence: 99%
“…Later, these authors reported enhanced reactivity by using dimeric catalyst 124 in hydrolytic kinetic resolution of terminal epoxides (Scheme 50) [108]. A recent synthetic application of kinetic resolution using primary alcohols was illustrated by the same authors in the total synthesis of (+)-reserpine via intermediate enone 125 [109]. The kinetic resolution of a racemic epoxide performed in acetonitrile with 4.5 mol% of catalyst 128 and benzyl alcohol as the nucleophile, afforded the secondary alcohol 126 in 41% yield and 96% ee, which was further converted into enone 125.…”
Section: Kinetic Resolutions Of Racemic Epoxides As Key Stepsmentioning
confidence: 99%